Gender Diversity in Ghanaian Boardrooms : An Abridged Report on Women on Boards of Corporate and Public Institutions in Ghana - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
This publication provides a baseline exploration into gender diversity in the Ghanaian boardroom.It examines gender diversity—across sectors, ownership types, legal status, listing status, and anumber of organizational and board-level characteristics— to provide empirical evidence to guidethe development of organizational and national policy. The study, launched in Accra in October 2016, mainly focused on generating a balanced and objective analysis of the issues surrounding women in the boardroom to ascertain the business case for having females on boards in Ghana. The objectives of the study were to examine the nature of gender diversity in public and private sector boards in Ghana, examine the determinants of board diversity in Ghanaian organizations, examine the relationship between gender diversity and organizational performance in Ghana, and to explore the experiences of women on boards. The first section of this report provides contextand background for the study, beginning with a summary of global trends in gender diversity and,more specifically, an overview of the regulatory and legal framework on gender diversity in Ghana.It also states the purpose of the study and cites significant previous studies. And it describes the research methodology used for this study. The second section presents and discusses the study’s findings, including a look at the firms sampled. It examines the nature of boards and gender diversity in Ghanaian boardrooms and explores gender dynamics within the corporate setting.The final two sections consider the implications of the study’s findings, particularly the challenges, prospects, and experiences of women on boards, followed by a presentation of conclusions and policy recommendations.